2017
DOI: 10.1103/physrevc.95.035502
|View full text |Cite
|
Sign up to set email alerts
|

Spin flip loss in magnetic confinement of ultracold neutrons for neutron lifetime experiments

Abstract: We analyze the spin flip loss for ultracold neutrons in magnetic bottles of the type used in experiments aiming at a precise measurement of the neutron lifetime, extending the one-dimensional field model used previously by Steyerl et al. [Phys. Rev. C 86, 065501 (2012)] to two dimensions for cylindrical multipole fields. We also develop a general analysis applicable to three dimensions. Here we apply it to multipole fields and to the bowl-type field configuration used for the Los Alamos UCNτ experiment. In all… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 36 publications
0
9
0
Order By: Relevance
“…High precision lifetime measurements were made at holding field strengths of 6.8 mT and 3.4 mT, and lower precision measurements at smaller fields down to 0.5 mT. The resulting lifetimes were fitted using a power law suggested by calculations of depolarization in the present trap geometry by Steyerl et al [22]: Neutrons can be heated by, for example, many small interactions with the vibrational motion of the UCN trap's magnetic field, slowly gaining enough energy to exceed the trap potential and escape from the trap during the long storage period. A limit on the uncertainty due to this effect was determined by looking for neutrons moving into the highest neutron detector position (38 cm above the bottom of the trap, or equal in height to the lowered cleaner), in run configurations B -E during the long storage time (see Table 1).…”
Section: Systematic Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…High precision lifetime measurements were made at holding field strengths of 6.8 mT and 3.4 mT, and lower precision measurements at smaller fields down to 0.5 mT. The resulting lifetimes were fitted using a power law suggested by calculations of depolarization in the present trap geometry by Steyerl et al [22]: Neutrons can be heated by, for example, many small interactions with the vibrational motion of the UCN trap's magnetic field, slowly gaining enough energy to exceed the trap potential and escape from the trap during the long storage period. A limit on the uncertainty due to this effect was determined by looking for neutrons moving into the highest neutron detector position (38 cm above the bottom of the trap, or equal in height to the lowered cleaner), in run configurations B -E during the long storage time (see Table 1).…”
Section: Systematic Uncertaintiesmentioning
confidence: 99%
“…High precision lifetime measurements were made at holding field strengths of 6.8 mT and 3.4 mT, and lower precision measurements at smaller fields down to 0.5 mT. The resulting lifetimes were fitted using a power law suggested by calculations of depolarization in the present trap geometry by Steyerl et al [22]: ) for an uncertainty on the measured neutron lifetime of 0.07 s. The 6.8 mT and 3.4 mT measurements showed no variation outside of statistics.…”
Section: Systematic Uncertaintiesmentioning
confidence: 99%
“…A small perpendicular holding field (on the order of 100 G) is provided inside the trap to help maintain polarization of trapped neutrons. Simulation work has shown that the expected dependence of the depolarization lifetime on the holding field strength is ∝ 1/B 2 hold [7], where B hold is the strength of the holding field. In the UCNτ experiment, the trap lifetime was measured as a function of B hold .…”
Section: Assesment Of Systematic Effectsmentioning
confidence: 99%
“…Ultracold neutrons in such traps are confined from above by the gravitational field of the Earth and from below and sides by a material that weakly absorbs neutrons and produces a potential barrier with the height V 0 300 neV [7,8,[10][11][12][16][17][18][19][20][21][22][23]. The latest measurements with such traps give [19] τ n = (881.5 ± 0.7 [stat] ± 0.6 [syst]) s. Since the neutron has a magnetic moment of 60 neV/T, the magnetogravitational capture of UCNs is possible [24][25][26][27][28]. The most accurate measurement of the lifetime of the neutron yields τ n = (877.7 ± 0.7 [stat] + 0.4 /− 0.2 [syst]) s [28].…”
Section: Introductionmentioning
confidence: 99%